Sistem za razporejanje in zmanjševanje stroškov proizvodnje - Bubenik, Peter (Strojniški vestnik, 2004)
This paper discusses the use of simulation techniques for work-order scheduling at the factory-floor level of production. The ability to implement a simulation effectively for factory scheduling is dependent upon the availability of shop-floor data and the response time for the evaluation process.
Keywords: razporejanje; načrtovanje proizvodnje; razporejanje delavniško; simuliranje; organizacija proizvodnje